The Effects of different Counseling Method toward Housewives Knowledge about Processing of the Household Waste - Rahmahdini, Rani; Vivanti, Diana; Heryanti, Erna (Biosfer: Jurnal Pendidikan Biologi, 2014)
A serious environmental problem has occurred due to the negative impact of household waste. Lack of knowledge and awareness of waste processing must be improved through an effective counseling method provided for housewives. The aim of this research was to determine different counseling methods about garbage toward housewives knowledge about processing of the household waste. This research carried out on Kampung Pulo, Jakarta Timur on April 2013. A quasi-experiment method with a randomized control group pretest-posttest design was used. Counseling methods of demonstration and movie display were given in two different groups as the treatment. Instrument of knowledge test was used to collect data. The normality testing of Kolmogorov-Smirnov test and the Homogeneity testing of F-test at Î± = 0.05 resulted a normal distribution and homogenous data. The hypothesis testing of t-test showed t count > t table on 3.34 > 2.03 which rejected the H0, meaning that different knowledge level about processing of the household waste obtained from different method of counseling. It is concluded that, demonstration method was more effective than movie display to increase the housewives knowledge about processing of the household waste.